2009
DOI: 10.1111/j.1365-313x.2009.03847.x
|View full text |Cite
|
Sign up to set email alerts
|

The MYB transcription factor GhMYB25 regulates early fibre and trichome development

Abstract: SUMMARYLittle is still known about the developmental control of the long seed coat trichomes of cotton (Gossypium hirsutum L.). In Arabidopsis, leaf trichome initiation is regulated by a group of well-defined transcription factors that includes MYB and homeodomain types. Many MYBs are expressed in fibres, but their roles in fibre development remain unclear. We analysed the function of one MYB transcription factor, GhMYB25, identified from transcriptome comparisons between wild-type and fibreless cotton mutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
290
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(305 citation statements)
references
References 28 publications
14
290
0
1
Order By: Relevance
“…Cotton seed hair development has a strong resemblance with Arabidopsis leaf trichome development [109]. The data generated from different studies using cotton fiberrelated genes supported this study, thus confirmed the close relationship between cotton seed fibers and Arabidopsis trichomes [110][111][112].…”
Section: Fiber Quality Traitssupporting
confidence: 68%
“…Cotton seed hair development has a strong resemblance with Arabidopsis leaf trichome development [109]. The data generated from different studies using cotton fiberrelated genes supported this study, thus confirmed the close relationship between cotton seed fibers and Arabidopsis trichomes [110][111][112].…”
Section: Fiber Quality Traitssupporting
confidence: 68%
“…Likewise, transcription factors participating in cotton fiber development have been reported by several studies. For example, a few MYB transcription factors were found to play important roles in cotton fiber initiation (Cedroni et al, 2003;Suo et al, 2003;Wang et al, 2004;Pu et al, 2008;Machado et al, 2009;Guan et al, 2011;Walford et al, 2011). In addition, it was recently reported that GbTCP (from sea-island cotton), which shares 47% protein sequence identity with GhTCP14, is involved in cotton fiber development, possibly through JA signaling (Hao et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…GhMYB25 belongs to a MIXTA type MYB transcription factor family and controls cotton fiber initiation. GhHOX3, a homologous gene of Arabidopsis HDG11/12, regulates plant epidermal cell differentiation (Nakamura et al 2006;Machado et al 2009). Significantly reduced gene expression of GbMYB25 and GbHOX3 in the TE-inserted cottons provided further evidence that GhHD1 is a critical upstream gene of GhMYB25 (Bedon et al 2014) and GbHOX3.…”
Section: Hd1 Is Critical To Stem Trichome Growth In Gossypiummentioning
confidence: 99%